PATHOPHYSIOLOGY STROKE NON-HEMORRHAGIC ET CAUSA THROMBUS - Wijaya, Aji Kristianto (E-Jurnal Medika Udayana; vol 2 no 10 (2013):e-jurnal medika udayana)
Normal 0 false false false EN-US X-NONE X-NONE Strok e is one of the most common cause of death worldwide and the third leading cause of death in the United States . Stroke composed 90,000 deaths of women and 60,000 men each year . In Indonesia , 8 of 1000 people suffered a stroke . Stroke is divided into two , non- hemorrhagic stroke and hemorrhagic stroke . Most of them (80%) is non-hemorrhagic stroke. Non- hemorrhagic stroke can be caused by thrombi or emboli . Understanding the pathophysiology of non- hemorrhagic stroke caused by a thrombus is very important in regard with providing appropriate patient managemen t . /* Style Definitions */ table.MsoNormalTable {mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-qformat:yes; mso-style-parent:""; mso-padding-alt:0in 5.4pt 0in 5.4pt; mso-para-margin-top:0in; mso-para-margin-right:0in; mso-para-margin-bottom:10.0pt; mso-para-margin-left:0in; line-height:115%; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Calibri","sans-serif"; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-fareast-font-family:"Times New Roman"; mso-fareast-theme-font:minor-fareast; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin; mso-bidi-font-family:"Times New Roman"; mso-bidi-theme-font:minor-bidi;}
Keywords: non-hemorrhagic stroke thrombus